Réponses

2014-04-02T12:09:54+02:00
A) (2x+3)²-49=(2x+3)²-7² de la forme a²-b²
(2x+3)²-7²=(2x+3+7)(2x+3-7)=(2x+10)(2x-4)=4(x+5)(x-2)

b) (2x+x)²-(4x+5)²=(3x)²-(4x+5)²
(2x+x)²-(4x+5)²=(3x+4x+5)(3x-4x-5)
(2x+x)²-(4x+5)²=(7x+5)(-x-5)=-(7x+5)(x+5)

c) 25-(3x-1)²=5²-(3x-1)²
25-(3x-1)²=(5+3x-1)(5-3x+1)
25-(3x-1)²=(3x+4)(6-3x)=3(3x+4)(2-x)

d) (4x+1)²-(7-2x)²=(4x+1+7-2x)(4x+1-7+2x)
(4x+1)²-(7-2x)²=(2x+8)(6x-6)=12(x+4)(x-1)
Meilleure réponse !
  • Utilisateur Brainly
2014-04-02T12:41:18+02:00
Factorisations:

a) 
(2x+3)² - 49
(2x+3)² -7²
(2x+3 -7) (2x+3 +7)
(2x-4) (2x+10)

b)
(2x+x)² - (4x+5)²
(2x+x -4x -5) (2x +x +4x +5)
(-x-5) (7x+5)

c)
25 - (3x-1)²
5² - (3x-1)²
(5-3x+1) (5+3x-1)
(-3x+6) (3x+4)

d)
(4x+1)² - (7-2x)²
(4x+1 -7+2x) (4x+1 +7-2x)
(6x-6) (2x+8)

Voilà ! J'espère t'voir aidé(e) ! :)